2022
DOI: 10.1177/20451253221090832
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effectiveness and cost effectiveness of clozapine for inpatients with severe borderline personality disorder (CALMED study): a randomised placebo-controlled trial

Abstract: Background: Data from case series suggest that clozapine may benefit inpatients with borderline personality disorder (BPD), but randomised trials have not been conducted. Methods: Multicentre, double-blind, placebo-controlled trial. We aimed to recruit 222 inpatients with severe BPD aged 18 or over, who had failed to respond to other antipsychotic medications. We randomly allocated participants on a 1:1 ratio to receive up to 400 mg of clozapine per day or an inert placebo using a remote web-based randomisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Nevertheless, our findings align with the previous Danish nationwide observational study that also found an association between treatment with clozapine and a reduction in psychiatric admissions in patients with BPD 18 . Altogether, to date, as the only RCT on clozapine failed to enroll a significant number of patients with BPD, 19 the evidence supporting the treatment of clozapine in BPD is primarily based on a few observational studies and single‐patient cases 35…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Nevertheless, our findings align with the previous Danish nationwide observational study that also found an association between treatment with clozapine and a reduction in psychiatric admissions in patients with BPD 18 . Altogether, to date, as the only RCT on clozapine failed to enroll a significant number of patients with BPD, 19 the evidence supporting the treatment of clozapine in BPD is primarily based on a few observational studies and single‐patient cases 35…”
Section: Discussionsupporting
confidence: 90%
“…In fact, just a handful of RCTs have been published in recent years. 19,27,28 However, there is ongoing industry-funded research on novel pharmacotherapeutic treatments for BPD. 29 In accordance with prior epidemiological research, 3,25 more than half of the patients were administered benzodiazepines and related drugs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations